2010
DOI: 10.1002/ffj.1967
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils and aromatic plants in animal feeding – a European perspective. A review.

Abstract: The last two decades have seen a substantial increase in the use of aromatic herbs and essential oils as feed additives in animal nutrition. One of the main reasons for this trend is to substitute antibiotic growth promoters, which have been completely banned as feed additives in the European Union since 2006 because they are suspected of contributing substantially to increasing resistance among human pathogens. Recent investigations have shown signifi cant antimicrobial eff ects of several essential oils and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
237
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(254 citation statements)
references
References 53 publications
(57 reference statements)
4
237
1
12
Order By: Relevance
“…The present results differ from those of Arafa et al (2010) who found, in a similar study using EPUR at 130 mg/kg BW, a significant decrease in the mortality rate and an increase in the live weight in 6-week-old growing rabbits fed E diets (P < 0.05). Dietary herb supplementation usually leads to an improvement in the flavour, which in turn accounts leads to an increase in feed ingestion and better performance (Franz et al, 2010;Christaki et al, 2012). Ahmed et al (2008) highlighted a significant improvement in the final BW, daily weight gain and feed conversion ratio in growing rabbits, which had orally been given 7.5 mg of EPUR extracts/kg BW/day in liquid form.…”
Section: Growth Performancesmentioning
confidence: 99%
“…The present results differ from those of Arafa et al (2010) who found, in a similar study using EPUR at 130 mg/kg BW, a significant decrease in the mortality rate and an increase in the live weight in 6-week-old growing rabbits fed E diets (P < 0.05). Dietary herb supplementation usually leads to an improvement in the flavour, which in turn accounts leads to an increase in feed ingestion and better performance (Franz et al, 2010;Christaki et al, 2012). Ahmed et al (2008) highlighted a significant improvement in the final BW, daily weight gain and feed conversion ratio in growing rabbits, which had orally been given 7.5 mg of EPUR extracts/kg BW/day in liquid form.…”
Section: Growth Performancesmentioning
confidence: 99%
“…Throughout history, herbs and spices and their constituent EO have been used as antiseptics, to preserve food and to enhance flavour (Shelef, 1984). More recently, EO have been used in animal feeds to combat infection and improve productivity (Wallace et al, 2002Newbold et al, 2004;Wallace, 2004;Franz et al, 2010). For example, EO and EO compounds, including thymol, carvacrol and eugenol, reduced the bacterial load in different parts of the gut and lowered the shedding of Clostridium perfringens in broiler chickens (Mitsch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among the major components in the oil are camphor, 1,8-cineole and artemisa ketone (Tzenkova et al, 2010). Essential oils often show strong antimicrobial properties in vitro, which is the reason why these compounds have gained much attention regarding their potential as alternatives to antibiotic growth promoters (Botsoglou et al, 2002;Lee et al, 2004;Brenes & Roura, 2010;Franz et al, 2010). Essential oil blends have shown promising results with respect to reduction of C. perfringens colonization and proliferation (Mitsch et al, 2004;Ivarsen et al, 2010;Timbermont et al, 2010).…”
mentioning
confidence: 99%